Isolasi, Identifikasi, Sifat Fisik, dan Biologi Virus Tetelo yang Diisolasi dari Kasus di Lapangan (ISOLATION, IDENTIFICATION, PHISICAL, AND BIOLOGICAL CHARACTER OF NEWCASTLE DISEASE VIRUS ISOLATED FROM FIELD CASES) - Wibowo, Michael Haryadi; Untari, Tri; Wahyuni, Anastasia Endang Tri Hastuti (Jurnal Veteriner, 2013)
native chicken farm suspected to Newcastle disease (ND) virus infection. Specimens were taken andcollected from the lung was further processed. Suspected materials were inoculated into allantoic sacc inspecific pathogenic free of 10 days embryonating egg chicken. The growth of the virus was determined withthe ability to agglutinate the chicken red blood cells or hemaglutination test. Positive hemaglutinationwas performed with hemaglutinatin inhibition test using specific antibody against ND virus. Method forND virus isolation, propagation and identification were based on the standard procedure of serologicalidentification for ND virus serological identification. 13 out of 34 samples were identified as ND viruses.Observation on the course and time of the virus to kill the chicken embryo could be differentiated intomoderate virus patho-type were 10 isolates and a virulent strains were 3 isolates. Further characterizationbased on the elution time observation indicated 11 isolates were not pathogenic strain and 2 isolates werenot virulent strain. Hemagglutinin stability study revealed that 11 isolates were sensitive being heated at560C for 30 minutes while 2 isolates were resistant. Biological characteristic of ND virus to hemagglutinateon various mammalian red blood cells indicating that most isolates were HA negative. Two isolates wereHA positive with cattle, horse and sheep red blood cell, and one isolate indicated positive HA test by usingsheep red blood cell. Control virus was lentogenic patho-type of La Sota strain showed HA and HI testpositive, elution time was 29 minutes, stability on the hemagglutinin after heating was 2 minutes and HApositive with cattle, horse and sheep red blood cell.
Keywords: Newcastle disease virus, virulence, hemagglutinin, elution